SUMY ALGEBRAICZNE:

1. zredukuj wyrazy podobne , a następnie oblicz wartość liczbową wyrażenia:
a) 5x - 7 + x + 15 - 2x dla x= 2
b) ½y - 3 - 2y + 5½y + ½ dla y= -1
c) -6x + 2y + 7 + 4x - 5y - 3 dla x= -0,5 , y= 0,1
d) 2x - 6y - 4y + 8 - 5x + y - 11 dla x= -1⅓ , y= jedna dziewiąta


rozpiszcie pliss :) ;*

2

Odpowiedzi

2010-03-27T15:56:27+01:00
A) 5x - 7 + x + 15 - 2x
dla x= 2
5x - 7 + x + 15 - 2x = 4x+8, podstawiamy:
4*2+8 = 16


b) ½y - 3 - 2y + 5½y + ½ dla y= -1
½y - 3 - 2y + 5½y + ½ = 4y-2½, podstawiamy:
4*(-1)-2½ = -4-2½ = -6½


c) -6x + 2y + 7 + 4x - 5y - 3 dla x= -0,5 , y= 0,1
-6x + 2y + 7 + 4x - 5y - 3 = -2x-3y+4, podstawiamy:
-2*(-0,5)-3*0,1+4 = 1-0,3+4 = 4,7


d) 2x - 6y - 4y + 8 - 5x + y - 11 dla x= -1⅓ , y= jedna dziewiąta
2x - 6y - 4y + 8 - 5x + y - 11 = -3x-9y-3, podstawiamy:
-3*(-1⅓)-9(1/9)-3 = 4-1-3 = 0
1 5 1
2010-03-27T16:13:11+01:00
A) 5x - 7 + x + 15 - 2x = 4x + 8
4*2+8= 8+8=16
b) ½y - 3 - 2y + 5½y + ½ =3y- 2½
-1*3-2½ = -3-2½ = -5½
c)-6x + 2y + 7 + 4x - 5y - 3 = -2x -3y +7
-0,5*-2 - 3*0,1+7 = 1-0,3+7= 7,7
d)2x - 6y - 4y + 8 - 5x + y - 11= -3x -10y -3